17 Burden of arrhythmias in non-surgical UK adult congenital heart disease (ACHD) centres: the norpap database. (28th April 2017) - Abraham, D; Rafiq, I; Lewis, C; Freeman, LJ
Abstract : Introduction: Adults with congenital heart disease have a high burden of arrhythmias related to the underlying substrate, and the consequences of palliation. The NORPAP ACHD database, established in 1993, contains 2587 patients in 2 non-surgical centres. Methodology: Patients with documented arrhythmias were extracted from the NORPAP database and analysed for demographics, underlying condition, surgical intervention, rhythm, and electrophysiological (EP) procedures between 1993 and 2015. Results: 13.6% of patients (353/2587) had documented arrhythmia, mean age 51 years, 50% male, prior surgical intervention in 77.9%. Atrial tachyarrhythmias predominate: Atrial Fibrillation (AF) 35.6%, Atrial Flutter (AFL) 24.3%, Supraventricular tachycardia (SVT) 19.5% and Atrial Tachycardia (AT) 8.2%. It was common for patients to experience more than one episode and type of arrhythmia. High grade AV Block in 8.5%, Sinus Node Dysfunction 3.4%. Ventricular Tachycardia (VT) 9.9%, Ventricular Fibrillation 0.6%. 32% of patients with arrhythmias had EP procedures, 82.4% had prior surgical intervention. Of the total, 88 had RF Ablation; 18% required repeat procedures. Underlying condition was diverse (21 conditions): Secundum ASD 19/88 (21.6%), Fallot's Tetralogy 19/88 (21.6%), and Ebstein's anomaly 9/88 (10.2%) were the most common. Conclusions: Whilst arrhythmias are most common in Secundum ASD, complex ACHD (ccTGA, complex congenital, TGA and Ebstein's anomaly) have a disproportionately high arrhythmia burden. 10% increase in EP procedures noted compared to our 2006 study. This is appropriate for to avoid recurrent admissions and long term anti-arrhythmics. Complex anatomy, challenging venous access and scar related re-entry tachycardias underline the need to expand the subspecialist EP-CHD capacity internationally.